The Effect of Regulation with Information Systems as a Moderate of Asset Management (Study on the Government of East Aceh District) - Azhar, Iqlima; Lubis, Nasrul Kahfi; Salman, Muhammad (Budapest International Research and Critics University, 2020)
This study aims to examine the effect of regulation with information systems as a moderating variable on asset management in the East Aceh District Government. The research was carried out on employees of the goods section of the East Aceh District Government Offices. Data collection was carried out through primary data, namely by distributing questionnaires to each respondent. Determination of the sample used in this study is the census method with a total sample of 44 people. Based on the MRA (Moderated Regression Analysis) test results, the multiple linear regression equation model is obtained as follows: Y = 1.322 + 0.702 Regulation + 0.222SI + 0.002 Regulation * SI, namely Regulation with Information Systems as moderating has a positive effect on asset management with a value a coefficient of 0.002.